Gênero e advocacia: obstatulos enfrentados pelas advogadas no exercício da profissão em Mossoró-RN - Silva, Amália Rosa de Moraes (Universidade Federal Rural do Semi-Árido, 2019)
The present work proposes to analyze the obstacles and discriminations faced by the female lawyers who work in the city of Mossoró/RN due to the condition of being a woman. To this end, we especially explore the category of gender from the perspective of feminism, which seeks to understand the oppressions that affect women in the face of the gender roles imposed on a patriarchal society. As the proposal is to analyze the situations experienced by the lawyers in the scope of their professional activity, we also discuss the participation of women in the labor market, the construction of the legal field in Brazil and how women were inserted in this area, exploring aspects of the opening of this niche in the job market for them. Finally, to analyze the experiences of women advocates in the city of Mossoró/RN, an online form was applied among them, aiming to draw a social profile of these professionals, as well as to collect data about the barriers encountered and the occurrence of discrimination and violence in their professional practice, seeking to expose situations of oppression and exclusion with which they must cope because of their gender, since advocacy and the legal field still have a greater number of men as professionals and that power relations between the sexes can reproduce in this area.
Keywords: Advocacia; Mercado de trabalho; Discriminação de gênero; Sociologia Jurídica; Advogadas; Job market; Gender discrimination; Female lawyers; Legal Sociology; CIENCIAS SOCIAIS APLICADAS::DIREITO